Securing fingerprint templates by enhanced minutiae‐based encoding scheme in Fuzzy Commitment. (1st April 2021) - Shukla, Shivangi; Patel, Sankita J.
Abstract: Fingerprint authentication has gained attention in recent years due to its distinctiveness, low‐cost sensors, and user willingness to submit them. Its extensive deployment in our automated world raises major concerns regarding the secrecy of biometric templates and the privacy of rightful owners in biometric systems. Fuzzy Commitment (FC) focuses on securing the biometric templates by performing authentication based on the validity of secret keys from biometric features. However, the major challenge in designing Fingerprint‐based FC is the requirement of efficient binary representation for unordered and variable minutiae points in fingerprint images. Additionally, its leakage can compromise an intrinsic characteristic of the individual. The paper proposes Fingerprint‐based FC incorporating an encoding scheme dependent on the number and type of minutiae points present near the fingerprint's core point. The biometric templates are never identical thereby, this approach allows fuzziness in minutiae points by incorporating Bose–Chaudhuri–Hocquenghem (BCH) codes for error‐correction and secures random codeword of the error‐correcting scheme as secret key by SHA‐256 hash mapping. The proposed approach is evaluated on FVC2000‐DB2, FVC2002‐DB1, FVC2002‐DB2, and FVC2004‐DB1, and the results illustrate the efficiency of the proposed scheme. Furthermore, the security analysis of stored helper data and hash mapping demonstrates that the proposed approach is secure.